Lactic acid bacteria from raw milk as potentially beneficial strains to prevent bovine mastitis - Espeche, Maria Carolina (2012)
Bovine mastitis produces a wide variety of problems in the dairy farm. The treatment of this disease is based on the use of antibiotics which are not always effective. These drugs are also responsible for the presence of residues in the milk and the increase of antibiotic-resistant strains. Probiotic products were proposed as a valid alternative to antibiotic therapies and are also useful for the prevention of infectious syndromes. With the aim of designing a probiotic product to prevent bovine mastitis, lactic acid bacteria (LAB) were isolated from foremilk samples from different dairy farms in Córdoba-Argentina. One hundred and seventeen LAB were isolated and their beneﬁcial characteristics such as the production of inhibitory substances, surface properties and production of exopolysaccharides (EPS) were assessed. Most of them displayed low degree of hydrophobicity, autoaggregation, EPS negative phenotype and were identiﬁed as Enterococcus hirae and Pediococcus pentosaceus. Nine LAB strains inhibited three indicator bacteria. Some isolates were pre-selected and genetically identiﬁed according to the results obtained. Antibiotic resistance and virulence factors were studied for the assessment of the safety of the strains. The results obtained were compared to those reported previously from samples obtained in the North-western area of the country and some differences were found.